A Historical Review of the Land Tenure and Registration System in Palestine - Najeh S. Tamim (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Due to its strategic location, Palestine has played a significant role in world politics. These politics, in turn, have been major influencing factors in the culture and history of Palestine. The land in Palestine has been, and still is, the central issue in the Palestinian - Israeli conflict; each claiming sovereignty over it. This paper will briefly outline the evolution of the land tenure and registration system in Palestine from the early days of Islam up to the present. A future methodology that may improve the current system will be proposed at the end of the paper.